Complicated fracture of the tooth 21 crown. Case presentation - Ana Gloria Vázquez de León; Alicia María Quiñones Betancourt; Laura María Regueira Llano (Medisur)
Dental trauma is frequently accompanied by psychological, aesthetic and social damage; hence their enormous social impact, they should be considered transcendent importance issues. Due to its low incidence, cases documented in the literature are a few; the objective of this report is to describe a case of the tooth 21 crown complicated fracture and its treatment. This is a 9-year-old female patient, with a health history, who came to the consultation after suffering a fall that caused a complicated fracture of the tooth 21crown. Treatment was initially performed, then clinical check-ups were carried out and radiographic. The presence of dental trauma is evident at any time in life. One or two teeth are usually affected, mainly the upper central incisors. Therapeutic behavior depends on factors such as type of trauma, the clinician's experience, and the establishment of appropriate care protocols.